Pigging Time Optimization Using Flow Efficiency Method and Flow Index Ratio in Wet Gas Pipeline (Case Study : Wet Gas Pipeline in Field - NUR AFI (NIM 12204058); Pembimbing: Dr.Ir. Leksono Mucharam, FUTIHA
The problem that often occurred in gas pipeline is the presence of condensation process. Condensation is a process of liquid forming caused by the difference of operating pressure and temperature in gas pipeline. Condensation can influence operating gas industry activities especially in gas pipeline transmission, because of the presence of condensate will decrease flow efficiency gas value. Flow efficiency is a value that shows the ability of pipeline flowing fluids. Pipeline has flow efficiency 100% if it can flow fluids perfectly without any barrier. In real condition there is not pipeline that has flow efficiency 100%, it is caused by several thing, such as roughness, friction, etc. Condensate forming in gas pipeline can be identified by pressure distribution pattern along pipeline or from its flow efficiency value. If condensate forming was indicated and value of flow efficiency has been low enough, operator would execute pigging process. It is a process to clean up pipeline from condensate. Because of there is not any technique that could give information when pigging process must be executed, until now operator execute pigging process frequently to keep flow efficiency value. If flow efficiency was so low, gas transmission process will be disturbed which caused producer suffer a loss. But too much pigging process also make a producer loss because of pigging cost is expensive. That is way, it is needed a better technique to identify a condensate presence and determine optimum pigging time. This paper is a study to determine optimum pigging time with case study pipeline in field "X" where fluid that flowed is wet gas.